A Composite Buccal Flap for Alar Based Defect Reconstruction: A Technical Note - F. Pourdanesh; A. Khojasteh (Tehran University of Medical Sciences, 2011)
It is difficult to reconstruct an alar defect with cartilage involvement. Here in the authors report a case of traumatic alar loss during childhood in which an alar reconstruction was carried out with a composite auricular graft put over the pedicle buccal flap which was rotated and passed through the intraoral side. The lining skin and auricular cartilage for the flap was obtained from the auricular region which was acceptable for the patient. All procedures were performed under general anesthesia. One year follow up revealed satisfactory results with minimal contracture of the graft.